Penggunaan Pengembangan Islam dan Ilmu Pengetahuan Kurikulum Berbasis Cinta Pengembangan Matari Ajar pada Sekolah Dasar - Ahmad Zainuri; Nabila Iffatul Maulana; Eva Yolanda Saputri; Frika Fatimah Zahra (Journal of Literature Review, 2025)
This study examines the integration of Islamic values and scientific knowledge through a love based curriculum approach in the development of learning materials for elementary school students. A curriculum grounded in the principle of love emphasizes compassion, empathy, and holistic character formation as fundamental elements in the learning process. The purpose of this study is to analyze how a curriculum inspired by love can support the spiritual, emotional, and intellectual development of learners, and how Islamic principles such as compassion, justice, and wisdom can be incorporated in a structured way into instructional content. This research uses a qualitative descriptive method by reviewing various literature sources, curriculum models, and practical applications in elementary school settings. The findings show that an Islamic curriculum based on love can strengthen student engagement, enhance moral awareness, and create a positive classroom environment that makes learning more meaningful and humanistic. The integration of scientific knowledge with Islamic perspectives also helps students understand knowledge in a complete and valuable way. This approach enriches academic comprehension and nurtures learners into empathetic individuals with strong ethical awareness. Overall, the study highlights the importance of curriculum innovation that unifies Islamic teachings, scientific literacy, and affective development to support comprehensive learning outcomes.